Thanatophobia (Death Anxiety) in the Elderly: The Problem of the Child’s Inability to Assess Their Own Parent’s Death Anxiety State - Sinoff, Gary (Frontiers in Medicine, 2017)
Thanatophobia is omnipresent in our lives. Research has shown separate but connected constructs: fear of death, or fear of the dying process. The influences on death anxiety are varied including religiosity, gender, psychological state and age. It is often assumed by the children of the elderly that the fear of death is prevalent in their parents. Daily the medical staff encounters the presence of death anxiety: from family members, or the staff itself. In order to understand this phenomenon, a three-tier study was conducted on non-terminal elderly in-patients in an acute geriatric care ward. The study showed that the elderly had low levels of anxiety (scoring 4/15 on Templer’s death anxiety scale) but their children scored higher for themselves (6.9/15) and for their parents (8.9/15). A regression model showed that only the presence of generalized anxiety and religiosity of parent had an effect explaining 33.6% of the variance. Death anxiety of death is usually absent in the elderly but rather they fear the dying process. On the other hand their children do fear death, which they extrapolate onto their parents. This causes conflicts since the children prevent disclosure of relevant medical information to their parents. This has to be addressed by the staff when dealing with family members, to allow open and honest communication with their patients. The staff need to explain to the family that the elderly are not afraid of death but of the suffering from the dying process.